SOD mediates mitochondrial epigenetic regulation in NIHL - Shi, Liuwei; Li, Caiping; Wang, Dianpeng; Lin, Dafeng; Yang, Xiangli; Li, Peimao; Zhang, Wen; Guo, Yan; Zhou, Liting; Zhang, Naixing (Frontiers in Cellular Neuroscience, 2025)
Occupational noise-induced hearing loss (NIHL) is linked to the overproduction of mitochondrial reactive oxygen species after noise exposure. This cross-sectional study investigated the relationship between mitochondrial DNA (mtDNA) D-loop region methylation and oxidative stress in 150 participants divided into three age and sex matched groups: a control group (n = 50, workers without noise exposure and with normal hearing), an exposed group (n = 50, workers with significant noise exposure but normal hearing), and a case group (n = 50, workers diagnosed with NIHL). The subjects among groups were matched for sex and age to control confounding factors. Methylation levels of the mtDNA D-loop region were determined by the quantitative PCR following bisulfite conversion, while mitochondrial DNA copy number (mtDNA-CN) was assessed using the real-time PCR. Oxidative stress markers—including superoxide dismutase (SOD), glutathione peroxidase (GPX), total antioxidant status (TAS), and malondialdehyde (MDA)—were quantified via substrate-specific assays, ultraviolet enzymatic methods, and colorimetric techniques. Results showed the case group (141.6 ± 46.80 U/mL) showed lower SOD than the control (159.5 ± 18.68 U/mL, p < 0.05) and exposed groups (164.0 ± 15.44 U/mL, p < 0.01), MDA was higher in the case group (232.8 ± 134.5 nmol/mL) than in the control (193.5 ± 84.13 nmol/mL) and exposed groups (187.3 ± 60.76 nmol/mL), with a significant overall difference (F = 3.162, p < 0.05). The case group showed lower methylation [1.205 (0.595, 2.748) %] than both the control [1.710 (0.912, 3.225) %] and exposed groups [1.850 (0.987, 4.093) %] (H = 7.492, p < 0.05). The case group exhibited higher mtDNA-CN levels [397.7 (205.9, 532.1)] compared to both the blank control group [317.4 (234.6, 549.6)] and the exposed group [225.1 (125.3, 445.0)] (H = 9.213, p < 0.05). Methylation levels of the D-loop region were positively correlated with SOD and negatively correlated with MDA. Mediation analysis indicated that SOD may mediate the relationship between D-loop methylation and bilateral high-frequency hearing thresholds, suggesting an indirect epigenetic regulatory mechanism. These findings imply that noise-induced oxidative imbalance, reflected by reduced SOD, may lead to D-loop hypomethylation, contributing to the development of NIHL. These methylation sites may serve as preliminary biomarkers for further research on preventive strategies.